Reaktualisasi Konsep Raḍā’ah Di Indonesia (Berdasarkan Studi Hermeneutika Qs. Al Baqarah [2]:233) - Nurpah Nurpah (Jurnal Studi Agama dan Masyarakat, 2016)
Lack of good nutrition for pregnant and lactating mothers cause reduced productivity smoothly for all mothers breastfeeding postpartum. Various problems that arise then in this study focuses on the obligations How can the mother in delivering the first food intake according to QS. Al-Baqarah [2]: 233. The type this study is a library research, where the data analysis method is double movement that popularized by Fazlur Rahman. Results  of  the  study  are:  Giving  exclusive  ASI  as  step  as  the commandement of Allah SWT.: “...and for mothers must do breastfeeding to their children as long as two years, its for the one who wan to give breastfeeding completely...” (QS. al Baqarah [2]:233). The recommendation of breastfeeding by giving ASI exclusively is being children‟s rightness. So, the porpose of maqasid syariah in order to life protection (ḥifẓ an nafs) and descent (ḥifẓ an nasl) can be realized. Formula milk (SUFOR) in order of its development has done some improvement of nutrition, still and all, the composition of SUFOR nutrition cannot compete the complete nutrition of exclusive ASI. The writer considers that the use of formula milk as the last way (mubah), is is if exclusive ASI cannot be gained by the baby.